2022
DOI: 10.1128/spectrum.00486-22
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitor-Induced Gut Dysbiosis Increases Mortality Rates for Patients with Clostridioides difficile Infection

Abstract: This article demonstrates that daily PPI use was the only avoidable risk factor for death. With more extended PPI use, the mortality rate was higher in patients with CDI. Decreases in Prevotella copri and Ruminococcus gnavus and increases in Parabacteroides merdae and Clostridioides difficile in line with daily PPI use duration were significantly associated with the death of CDI patients. Our findings provide in-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…play a key role in regulating human microbiome health and are mostly associated with oral infections. In fact, a newly published study found that the relative abundance of Prevotella copri and Ruminococcus gnavus is inversely correlated with the duration of PPI use in patients with CDI [ 54 ], which supports the discovery of the decrease in the abundance of Paraprevotella , Prevotella 2 , and Prevotella 9 belonging to the Prevotellaceae family in our results. The altered abundance of Prevotella caused by the use of PPIs might therefore worsen infection and be associated with some risk factors for inflammatory diseases.…”
Section: Discussionsupporting
confidence: 91%
“…play a key role in regulating human microbiome health and are mostly associated with oral infections. In fact, a newly published study found that the relative abundance of Prevotella copri and Ruminococcus gnavus is inversely correlated with the duration of PPI use in patients with CDI [ 54 ], which supports the discovery of the decrease in the abundance of Paraprevotella , Prevotella 2 , and Prevotella 9 belonging to the Prevotellaceae family in our results. The altered abundance of Prevotella caused by the use of PPIs might therefore worsen infection and be associated with some risk factors for inflammatory diseases.…”
Section: Discussionsupporting
confidence: 91%
“…As dietary change is an external factor that alters the gut microbiota, an initial increase in diversity may have occurred in the high-dose group. In addition, increased diversity of the gut microbiota can positively affect host health by maintaining gut homeostasis ( 27 ), whereas decreased diversity is associated with various gastrointestinal, metabolic, and immune diseases, indicating dysbiosis of the gut microbiota ( 28 , 29 ). Thus, red ginseng dietary fiber may improve host health by increasing gut microbial diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Among these selected species, there are species that are known commensals such as Faecalibacterium prausnitzii and Bacteroides thetaiotaomicron 62 and species that are known to co-colonize with C. difficile such as Klebsiella pneumoniae , 63 and species that are reported to provide some protection against CDI such as Prevotella copri and Ruminococcus gnavus . 64 …”
Section: Discussionmentioning
confidence: 99%